Aspectos da biologia de nidificação de abelhas solitárias no maciço de Baturité, Ceará - Brasil, Michelle de Oliveira Guimarães (2015)
The aim of this thesis was to study the structure of the community of bees which nest in pre-existing cavities in remnants of Atlantic Forest of Maciço de Baturité - Ceará. Therefore, it was verified the occupation and emergency of bees which nesting in trap-nests and assessed the aspects of the structure of such nests, sex ratio, mortality, preference for different kinds of substrates and diameters besides the presence of natural enemies of these species in four areas of the region, aiming their use in pollination management programs. The samples were carried out using three types of trap-nests: buds of dried bamboo, cardstock tubes and rational boxes. In the four areas of humid mountain forest studied were occupied 34 artificial nests by bees. Six species of nesting bees were sampled, distributed in five genera (Centris, Mesocheira, Euglossa, Megachile and Coelioxys) and two families (Apidae and Megachilidae). Out of the total of nests recorded with emergency it was obtained 139 individuals, being 131 bees and 8 coleopterans. In the 34 nests obtained, 162 bee brood cells were built, with the number of cells per nest-trap ranging from 1 to 13 brood cells and the length of these ranging from 2.4 to 14 cm. Thirteen nests were parasitized by hymenopterans (Apidae and Megachilidae) and coleopterans (Meloidae), resulting in a parasitism rate of 38.2% of nests founded. In addition, mortality has occurred from unknown causes in 29.4% of subjects before reaching adult stage. The bees nested in the three types of traps available, being buds of dried bamboo the most widely used by the species of bees to build their nests (p <0.05), corresponding to 82% out of the total used. The bees showed a greater preference for nesting into holes with smaller diameters. It is concluded that the data presented are important for the performance of practices that aim at maintenance and conservation of these species, and may be useful for pollination services of native and agricultural plants of that region.